KEBIJAKAN FREE AND OPEN INDO-PACIFIC (FOIP) JEPANG: IMPLIKASINYA TERHADAP KEAMANAN MARITIM INDONESIA - Nadirah, Nadirah; Oracle, Yusuf Nirendra (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the impact of Japan's Free and Open Indo-Pacific (FOIP) policy on Indonesia’s maritime security. The research adopts a qualitative descriptive method, utilizing document-based analysis through literature review of official records, academic journals, books, and reports from international organizations. The theoretical framework draws on liberalism in international cooperation and world-systems theory to understand maritime security dynamics in the Indo-Pacific region. The findings indicate that Japan’s implementation of FOIP through defense cooperation, maritime security training, patrol vessel assistance, and multilateral diplomacy has significantly enhanced Indonesia’s maritime surveillance, law enforcement capabilities, and protection of major sea lines of communication. Moreover, FOIP strengthens the observance of international maritime law and supports Indonesia’s position in addressing non-traditional security threats. Thus, FOIP has positively contributed to Indonesia’s maritime security through strategic bilateral and regional collaboration.